LIVING CONDITIONS, NTRA-SOCIETAL TRUST, AND PUBLIC CONCERNS IN POST-SOCIALIST TURKMENISTAN - DADABAEV, Timur (CENTRAL ASIA AND THE CAUCASUS, 2006)
Turkmenistan’s important role in the regional and world economy, in its post-independence period, is cemented by its large reserves of oil, gas, and other energy resources.1 Yet there is little evidence that this economic potential and the enormous revenues materialized in the population’s improved well-being. Although Turkmenistan is considered to be a lower middle level income country, little progress, if any, has been recorded from the time of its independence, especially in the areas of political and social reform. Its political development is shadowed by the one-man rule of President-for-Life Saparmurat Niyazov, who claims to be the father of the nation.2 Consequently, no area of social life is beyond the president’s reach. A wide range of presidential orders prohibited smoking, closed rural hospitals,3 renamed the months of the year after the President and his relatives, shortened the educational period,4 introduced the President’s own book into the education curriculum, and prohibited long hair, beards, and car radios.5 There is also a prohibition on opera and ballet because the President considered them to be inappropriate for Turkmen culture